Ultra-high resolution band-selective HSQC for nanomole-scale identification of chlorine-substituted 13 C in natural products drug discovery - Wang, Xiao (Magnetic resonance in chemistry : MRC, 2017)
Copyright © 2016 John Wiley & Sons, Ltd.